2016
DOI: 10.1038/mtm.2016.76
|View full text |Cite
|
Sign up to set email alerts
|

Robust generation of transgenic mice by simple hypotonic solution mediated delivery of transgene in testicular germ cells

Abstract: Our ability to decipher gene sequences has increased enormously with the advent of modern sequencing tools, but the ability to divulge functions of new genes have not increased correspondingly. This has caused a remarkable delay in functional interpretation of several newly found genes in tissue and age specific manner, limiting the pace of biological research. This is mainly due to lack of advancements in methodological tools for transgenesis. Predominantly practiced method of transgenesis by pronuclear DNA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…recently developed a novel method for direct transfection of testicular germ cells that provides a nonviral, nonsurgical alternative for nucleic acid delivery. This technique uses a buffered salt solution to generate an osmotic gradient that drives water and dissolved linear DNA into the germ cells of the testis at a reasonably high rate (Usmani et al 2016). Once inside the cells, the DNA integrates spontaneously and randomly into the genome at a concentration-dependent rate, presumably through nonhomologous end joining during routine DNA repair.…”
Section: Resultsmentioning
confidence: 99%
“…recently developed a novel method for direct transfection of testicular germ cells that provides a nonviral, nonsurgical alternative for nucleic acid delivery. This technique uses a buffered salt solution to generate an osmotic gradient that drives water and dissolved linear DNA into the germ cells of the testis at a reasonably high rate (Usmani et al 2016). Once inside the cells, the DNA integrates spontaneously and randomly into the genome at a concentration-dependent rate, presumably through nonhomologous end joining during routine DNA repair.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, He et al [53] demonstrated that the transgene transmission rate from F0 to F1 generation was 37%, suggesting that the transgene transmission rate was similar to the Mendelian law of inheritance. In 2007 and onward, attempts to improve IIGT systems were made by several laboratories to enhance the gene delivery efficiency [54][55][56][57][58][59][60][61][62][63][64][65][66][67]. In the following sections, we will describe several examples [(v) to (x)] about the improvement of IIGT, in vitro assessment for gene expression after IIGT or possible mechanism underlying IIGT.…”
Section: Historical Background Of Tmgt-related Experiments 21 Iigt-rmentioning
confidence: 99%
“…To overcome this difficulty, they developed an alternative technique for making Tg mice by hypotonic shocking male germ cells for gene delivery. According to Usmani et al [65], treatment with hypotonic Tris-HCl solution reduced osmolarity and led to hypotonic-swelling of germ cells. The hypotonic-swelling eventually killed the cells with increased hypotonicity, but led to the uptake of surrounding molecules such as nucleosides inside the cell.…”
Section: Historical Background Of Tmgt-related Experiments 21 Iigt-rmentioning
confidence: 99%
See 2 more Smart Citations